Potensi Emisi Gas Rumah Kaca dari Pengolahan Limbah Peternakan Sapi Potong pada Peternakan Rakyat di Kecamatan Paseh Kabupaten Sumedang - Pauzan, Irpan; Falahudin, Oki; Falahudin, Aaf (Tropical Livestock Science Journal, 2024)
The purpose of this study was to analyze the potential for reducing GHG emissions through composting beef cattle waste in the Livestock Farmers Group in Paseh District, Sumedang Regency. The method used in this study was observational and survey research. The data obtained were analyzed descriptively. The data used in this study were primary data from interviews with 53 livestock farmers in Paseh District. Direct physical observations in the field and questionnaire data. The data obtained were analyzed using the Tier-1 method in the 2006 IPCC Guidelines. The stages in calculating gas emissions include: Determining the number of populations (animal units), namely the number of populations (Animal Units) obtained from the results of multiplying the number of populations by the correction factor set for beef cattle. Calculation of Methane (CH4) Gas Emissions from beef cattle feces management was carried out using the Tier-1 method in IPCC (2006). The results of the study revealed that the main sources of emissions were enteric fermentation of 0.0669 Gg CO2-eq/year, waste processing of 0.0014 Gg CO2-eq/year, N2O emissions directly from feces processing of 290.232 Gg CO2-eq/year and indirect emissions from beef cattle feces waste processing of 0.098 Gg CO2-eq/year. The conclusion is that beef cattle waste processing in Paseh District, Sumedang Regency, contributes to reducing greenhouse gas (GHG) emissions, especially methane (CH4) and nitrous oxide (N2O).